Batoid fishery in Peru (1950-2015): Magnitude, management and data needs (Revista de Biología Marina y Oceanografía, 2023)
Historical landings from the Food and Agriculture Organization (1950–2015) were used to estimate the contribution of the Peruvian batoid fishery to the eastern Pacific Ocean, and species-specific landings from Instituto del Mar del Peru (1997-2015) were used to identify the most-landed species, their landings sites and monthly variation throughout the year, and fishing gear types most used. The regulatory and research landscape were evaluated toward identifying potential gaps that may be hindering conservation and management of batoids in Peru. Results showed that in the eastern Pacific, Peru ranked second, after Chile, for batoid landings from 1950 to 2015. Of the twenty-three species of marine batoids that interact with Peruvian fisheries, the most landed taxonomic groups, from 1997 to 2015, were: Myliobatis spp. (i.e., M. chilensis and M. peruvianus; 45% of batoids landings), Mobula spp. (primarily M. mobular, and secondarily M. thurstoni, M. munkiana, M. tarapacana; 28%), Pseudobatos planiceps (6%), and Hypanus dipterurus (6%). Most of these species are landed in northern Peru, where gillnets are the most-used fishing gear to capture them. Batoid landings occurred year-round; yet, for H. dipterurus and P. planiceps landings were highest during the austral summer. Only three management measures exist for batoids fisheries in Peru for three species (i.e., M. birostris, Pristis pristis, Rhinoptera steindachneri) and two taxa (i.e., Mobula and Myliobatis) which are not fully enforced. Batoid research in Peru is limited, with only 25 publications from 1978 to 2022, in which the most studied species are Mobula birostris, M. chilensis and M. peruvianus. This study establishes an information baseline for batoids in Peru that can help guide their management, research, and conservation.